The influence of social media and celebrity endorsers on culinary purchase intention by viral marketing as a mediating variable - Telsi Divya; Susi Evanita (Operations Management and Information System Studies, 2021)
This paper aims to determine the influence of social media (foodgram) and celebrity endorser on purchase intention culinery in Padang viral marketing as the mediation variable. The sample in study is 100 in Padang Society. Data processed using Smart PLS 3.0. The result of this research are: (1) social media has a positive and significant effect on purchase intention culinery in Padang, (2) celebrity endorser has a possitive and significant effect on purchase intention culinery in Padang, (3) social media has a positive and significant effect on viral marketing,(4) celebrity endorser has a positive and significant effect on viral marketing, (5) viral marketing has a possitive and significant on purchase intention culinery in Padang, (6) social media has a positive and significant effect on purchase intention culinery in Padang with viral marketing as the mediation variable, (7) celebrity endorser has a positive and significant effect on purchase intention culinery in Padang with viral marketing as the mediation variable.